Analisis Pengaruh Gaya Hidup Konsumtif Terhadap Kondisi Keuangan Mahasiswa - Anis Afriani; Prestasya Prestasya; Adel Putri Lestari; Aulia Sari (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The increasing tendency of consumptive lifestyles among university students has become a significant concern due to its potential impact on personal financial stability. This study aims to analyze the influence of consumptive lifestyle patterns on the financial condition of students in the contemporary digital era, where social media trends and online shopping platforms strongly affect spending behavior. This research employed a quantitative approach using a survey design. Data were collected through questionnaires distributed to 100 university students selected through purposive sampling and analyzed using descriptive statistics and simple linear regression. The findings indicate that a consumptive lifestyle has a significant negative effect on students’ financial conditions. Students with higher levels of consumptive behavior tend to experience difficulties in managing expenses, saving money, and maintaining financial balance. The study concludes that excessive consumption behavior contributes to financial vulnerability among students and highlights the importance of financial literacy and budgeting skills. Theoretically, this research enriches the literature on consumer behavior and personal finance among young adults. Practically, the findings may assist educational institutions and policymakers in developing financial education programs. The originality of this study lies in its focus on the interaction between consumptive lifestyle trends and student financial well-being within the context of the digital economy.